Combined treatment of disulfiram with PARP inhibitors suppresses ovarian cancer - Tang, Bin; Wu, Min; Zhang, Lin; Jian, Shuyi; Lv, Shiyi; Lin, Tongyuan; Zhu, Shuangshuang; Liu, Layang; Wang, Yixue; Yi, Zhengfang; Jiang, Feiyun (Frontiers in Oncology, 2023)
Due to the difficulty of early diagnosis, nearly 70% of ovarian cancer patients are first diagnosed at an advanced stage. Thus, improving current treatment strategies is of great significance for ovarian cancer patients. Fast-developing poly (ADP-ribose) polymerases inhibitors (PRAPis) have been beneficial in the treatment of ovarian cancer at different stages of the disease, but PARPis have serious side effects and can result in drug resistance. Using PRAPis in combination with other drug therapies could improve the efficacy of PRAPis. In this study, we identified Disulfiram as a potential therapeutic candidate through drug screening and tested its use in combination with PARPis. Cytotoxicity tests and colony formation experiments showed that the combination of Disulfiram and PRAPis decreased the viability of ovarian cancer cells. The combination of PRAPis with Disulfiram also significantly increased the expression of DNA damage index γH2AX and induced more PARP cleavage. In addition, Disulfiram inhibited the expression of genes associated with the DNA damage repair pathway, indicating that Disulfiram functions through the DNA repair pathway. Based on these findings, we propose that Disulfiram reinforces PRAPis activity in ovarian cancer cells by improving drug sensitivity. The combined use of Disulfiram and PRAPis provides a novel treatment strategy for patients with ovarian cancer.